Application of optical reflectometer for monitoring corrosion process - Kochanowicz, Marcin; Markiewicz, Jakub (Photonics Letters of Poland, 2022)
In this work, a corrosion sensor based on an optical time domain reflectometer was presented. The first sensor with a bare tip was used to measure the corrosion process of silica glass fiber. Another sensor with a deposited silver layer was used for monitoring the corrosion process in nitric acid. In both cases, reflectance at the end of the fiber was decreasing with immersion time. Thus we can describe the corrosion stage by the level of fresnel reflectance. The maximum sensitivities of the analyzed sensors were as follows: 0.7dB/min (3% HF solution) 0.15dB/h (5%HNO3 solution) Results showed that the corrosion process in all cases wasn’t fully linear, and all reactions began almost instantly after immersing sensors in tested corrosive environments. Full Text: PDF References C. Elosua, F.J. Arregui et al., "Micro and Nanostructured Materials for the Development of Optical Fibre Sensors", Sensors, 17, 2312 (2017). CrossRef B.H. Lee, Y.H. Kim et al., "Interferometric Fiber Optic Sensors", Sensors, 12, 2467 (2012). CrossRef X. Wang, O.S. Wolfbeis, "Fiber-Optic Chemical Sensors and Biosensors" (2013-2015), Analytical Chemistry, 88, 203 (2016). CrossRef M.A. Butler, "Fiber Optic Sensor for Hydrogen Concentrations near the Explosive Limit", J. Electrochem. Soc., 138, 46 (1991). CrossRef M.A. Butler, "Optical Fiber hydrogen sensor", Appl. Phys. Lett. 45, 1007 (1984). CrossRef S.F. Silva, L. Coelho et al., "A Reviev of Palladium-Based Fiber-Optic Sensors for Molecular Hydrogen Detection", IEEE Sens. J., 12, 93 (2012). CrossRef C. Floridia, F.C. Salgado et al., "Methane leak detection and spectral analysis by using only optical time domain reflectrometry in semidistributed remote optical sensors", IEEE Sens., 2016. CrossRef J.F. Martins-Filho, E. Fontana et al., Fiber-optic-based Corrosion Sensor using OTDR, IEEE SENSORS 2007 Conference (2007). CrossRef E.A. Lima, A.C. Bruno, "Improving the detection of Flaws in Steel Pipes Using SQUID Planar Gradiometers", IEEE Trans. Appl. Supercond. 11, 1299 (2001). CrossRef J. Yin, J. Pineda de Gyvez et al., "Real-Time Full Signature Corrosion Detection of Underground Casing Pipes", IEEE Instrumentation and Measurement Technology Conference (1996). CrossRef H. Park, D. Kim et al., "HF etched glass substrated for improved thin-film solar cells", Heliyon, 4, 10, (2018). CrossRef M. Mozammel, "Kinetics of Silver Dissolution in Nitric Acid from Ag-Au0:04-Cu0:10 and Ag-Cu0:23 Scraps", J. Mater. Sci. Technol., 22, 696 (2006). DirectLink